Calla lily soft rot causal agents, symptoms, virulence and management: a review - Niyokuri, A. N.; Nyalala, S. (International Journal of Horticultural Science, 2023)
Bacterial soft rot is a polyetiological disease attacking calla lily [Zantedeschia spp (L.) Spreng.]. This disease has reduced the commercial value of this crop. This work aims to review scientific information to give an insight into calla lily soft rot causal agents, symptoms, factors favouring the disease, virulence mechanisms and management strategies. Special emphasis is put on the current progress with regards to understanding calla lily mechanisms of resistance to soft rot and their potential for the development of tolerant/resistant cultivars with commercial traits.